The Influence of KARS Accreditation Status (Paripurna vs. Non-Paripurna) on Patient Satisfaction Ratings: A Case Study of Public Sentiment Analysis on Google Maps Reviews - Rafika Aini; Mila Sari (Journal of Health Service Administration and Hospital Management, 2025)
The quality stability of healthcare services in Indonesia is critically influenced by the Hospital Accreditation Commission (KARS) certification, which functions as a formal regulatory system ensuring compliance with national standards. Despite this, a gap persists between formal accreditation status (Paripurna vs. Non-Paripurna) and actual patient satisfaction, particularly as reflected in public sentiment on digital platforms like Google Maps. This study aims to analyze the correlation between KARS accreditation levels and patient satisfaction ratings derived from sentiment analysis of over 50,000 Indonesian-language Google Maps reviews spanning 2020–2025. Employing a quantitative correlational design, the research integrates ordinal accreditation data and sentiment classification results generated through advanced machine learning methods (LSTM/Naïve Bayes). The analysis utilized Spearman’s rank correlation to assess the association between hospital accreditation status and aggregated sentiment scores. Findings reveal a statistically significant but weak positive correlation (ρ = 0.215, p < 0.001), indicating that higher formal accreditation does not strongly predict better patient-perceived quality. Negative sentiments notably cluster around non-technical service issues such as staff empathy and administrative delays, highlighting deficiencies unaddressed by the accreditation framework. These results suggest the need for hospital management and policymakers to incorporate digital patient feedback as a critical complement to traditional quality assurance measures. The study advocates for integrating Patient Reported Experience Measures (PREMs) from online sources into KARS standards and encourages future research using diagnostic tools like Root Cause Analysis to target underlying causes of patient dissatisfaction. This comprehensive approach aims to close the gap between institutional compliance and patient experience, promoting sustainable improvements in healthcare service quality in Indonesia.